Detecção de falhas em motores elétricos utilizando aprendizado de máquina - Novais, Leonardo Rezende (Universidade Federal de São Carlos, 2023)
This work proposes a method for detecting failures in electric motors, using machine learning techniques. For training and testing of the model, a data base containing 1951 time series obtained from 4 different sensors that simulate 6 states of operation: normal, unbalanced, horizontal misalignment, vertical misalignment, internal bearing failure and external bearing failure.
Detection of failures in electric motors using machine learning
Keywords: Aprendizado de máquina; Motores elétricos; Detecção de falhas; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS::AUTOMACAO ELETRONICA DE PROCESSOS ELETRICOS E INDUSTRIAIS